2014
DOI: 10.1155/2014/634874
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis and Proliferation Index in Patients with Acute Leukemia: A Prospective Study

Abstract: Angiogenesis and proliferation as measured by microvessel density (MVD) and proliferation index (PI) are essential correlates of malignancy. The aim of our study was to evaluate difference between these values in AML and ALL and also to study the modulation in these parameters following achievement of remission in acute lymphoblastic leukemia. Differences between adult and adolescent cases of acute leukemia in relation to these values were also studied. We also tried to assess the relationship between angiogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
13
1
Order By: Relevance
“…Other studies confirmed the increased MVD in AML bone marrow and showed also a correlation between the increase of MVD and the proliferation index of leukemic blasts [56] and the association between increased MVD and increased bone marrow VEGF levels, both parameters decreasing in patients who achieved disease remission following induction therapy [57] . Kuzu et al [58] showed a higher MVD in AML patients compared to controls, independent of cellularity or blast percentage; higher baseline MVD values in AML patients were associated with a shorter overall survival and thus are a negative prognostic factor.…”
Section: Angiogenesis In Aml Bone Marrow: Microvessel Densitymentioning
confidence: 76%
“…Other studies confirmed the increased MVD in AML bone marrow and showed also a correlation between the increase of MVD and the proliferation index of leukemic blasts [56] and the association between increased MVD and increased bone marrow VEGF levels, both parameters decreasing in patients who achieved disease remission following induction therapy [57] . Kuzu et al [58] showed a higher MVD in AML patients compared to controls, independent of cellularity or blast percentage; higher baseline MVD values in AML patients were associated with a shorter overall survival and thus are a negative prognostic factor.…”
Section: Angiogenesis In Aml Bone Marrow: Microvessel Densitymentioning
confidence: 76%
“…Next, we separately analyzed the relationships between the drug sensitivity of tumor cells of patients with primary AML and the expression of lymphoid (T- and B-) and immature markers as well as the proliferation marker, Ki-67, which are indicators of an unfavorable prognosis for leukemia [39,40,41,42]. Resistance of tumor cells to doxorubicin correlated only with the expression of one T-cell marker, CD2 ( r = 0.51), whereas resistance to daunorubicin correlated directly with the expression of several T-cell markers (CD2, r = 0.16; CD3, r = 0.38; CD7, r = 0.07; and CD11c, r = 0.41), and the natural killer (NK) cell marker, CD56 ( r = 0.50).…”
Section: Resultsmentioning
confidence: 99%
“…However, there is strong evidence of increased angiogenesis in these "liquid" tumors as well. Increased microvessel density and/or infiltration of inflammatory cells is seen in bone marrow of patients suffering from virtually all types of HM [84,[108][109][110][111][112][113][114]. Increased microvessel density and endothelial cell mass plays an important role in providing nutrients and oxygen to malignant cells.…”
Section: Nanomedicines For Drug Delivery In Hematological Malignanciesmentioning
confidence: 99%